Economic Growth at a Maximal Rate - Koopmans, Tjalling C. (Quarterly Journal of Economics, 1964)
I. Introduction, 355. — II. A model with two commodities, 359. — III. Growth paths and proportional growth paths, 361. — IV. Geometrical representation of the technology, 362. — V. Representation of proportional growth, 366. — VI. Determination of a maximal proportional growth path, 367. — VII. A price system sustaining a given von Neumann path, 370. — VIII. Is any proportional growth path sustained by a price system maximal? 374. — IX. A numerical example, 375. — X. The turnpike conjecture, 377. — XI. Access to or from the von Neumann path, 378. — XII. Rates of growth in von Neumann value, 379.— XIII. “Profit” effects of an interest rate reduction, 382. — XIV. A variant of Radner's turnpike theorem, 383. — XV. A catenary property of maximal growth paths, 385. — XVI. The turnpike conjecture in other cases, 387. — XVII. Concluding remarks, 391.